Lactoferrin exhibits PEDV antiviral activity by interfering with spike-heparan sulfate proteoglycans binding and activating mucosal immune response - Liu, Peng; Zuo, Jinjiao; Lu, Hui; Zhang, Bin; Wu, Caihong (Veterinary research (Paris), 2025)
Neonatal piglets infected with Porcine Epidemic Diarrhea Virus (PEDV) experience a mortality rate of up to 90%, resulting in significant economic losses to the swine industry in China. Current strategies using specific antibodies in sow milk to prevent Porcine Epidemic Diarrhea (PED) in these piglets through specific antibodies in sow milk is unsatisfactory. Preliminary studies have shown limited success. Emerging evidence suggests that general immune factors in sow milk provide protection to neonatal piglets, particularly, lactoferrin, play a crucial role in protecting piglets by inhibiting PEDV replication. However, the precise mechanism by which lactoferrin exerts its antiviral effects remains unclear. This study sought to clarify these mechanisms through both in vitro and in vivo approaches, proposing that higher concentrations of lactoferrin lead to greater antiviral activity. It was hypothesized that lactoferrin can impede PEDV by blocking its binding to heparan sulfate proteoglycans (HSPG) on the surface of target cells, and molecular docking experiments was conducted to identify the binding sites between lactoferrin and HSPG. Additionally, the findings indicated that lactoferrin can effectively trigger the maturation of porcine dendritic cells and boosts their antigen-presenting functions, thereby improving intestinal mucosal immunity in neonatal piglets against PEDV. Overall, these findings aid to elucidate the antiviral actions and mechanisms of lactoferrin in sow colostrum, offering new insights for the effective prevention and control of PED in neonatal piglets.